Teacher Role as Professional Educator in School Environment - Andika Dirsa; Silvia Anggreni BP; Chanti Diananseri; Ilham Setiawan (International Journal of Science Education and Cultural Studies, 2022)
Teachers play an essential and strategic role in education. This is because the teacher is a component of education and is at the forefront of carrying out educational goals. This educational component impacts improving the quality of teaching and students' character in schools. The teacher works directly with students to instil science and technology and instil positive values ​​by leading and setting good examples. The method in this study uses a qualitative approach with the type of library research, in which the researcher collects data from literary sources such as books and journals and utilizes online sites and other relevant references. Related. After data analysis, it can be concluded that the teacher plays an essential role in school and society. From the point of view of society, teachers are people who provide education in a particular field. Teachers have a respectable position in society. Starting from his position as a teacher, he must show the correct behaviour as a teacher and make it the norm in all situations inside and outside the school according to society's expectations.